Comparative analysis of medicinal plants used in traditional medicine in Italy and Tunisia - Ghedira Kamel; Leporatti Maria (BMC, 2009)
Abstract Background Italy and Tunisia (Africa for the Romans), facing each other on the opposite sides of the Mediterranean Sea, have been historically linked since the ancient times. Over the centuries both countries were mutually dominated so the vestiges and traces of a mutual influence are still present. The aim of the present study is to conduct a comparative analysis of the medicinal species present in the respective Floras in order to explore potential analogies and differences in popular phytotherapy that have come out from those reciprocal exchanges having taken place over the centuries Methods The comparative analysis based on the respective floras of both countries takes into consideration the bulk of medicinal species mutually present in Italy and Tunisia, but it focuses on the species growing in areas which are similar in climate. The medicinal uses of these species are considered in accordance with the ethnobotanical literature. Results A list of 153 medicinal species belonging to 60 families, present in both floras and used in traditional medicine, was drawn. A considerable convergence in therapeutic uses of many species emerged from these data. Conclusion This comparative analysis strengthens the firm belief that ethno-botanical findings represent not only an important shared heritage, developed over the centuries, but also a considerable mass of data that should be exploited in order to provide new and useful knowledge.